SINKRONISASI KEBIJAKAN NASIONAL REDD+ DENGAN KEPENTINGAN PARA PIHAK PADA TINGKAT SUBNASIONAL - Mimi Salminah; Ari Wibowo (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2017)
REDD+ has been developed since 2007, but its implementation has not been run effectively. Synchronizing all related stakeholders' interest, either horizontally or vertically becomes major challenge to support the effectiveness REDD+ implementation. The result of the gap analysis showed that unsynchronized REDD+ national policy with stakeholders' interest in subnational and site level lead to ineffective REDD+ implementation. This is particularly when REDD+ is developed through subnational approach by which provincial government plays as a main actor in its implementation. For instance, ban of carbon market system has caused some REDD+ projects in the site level initiated by private sector to be stagnant. Enabling conditions should be built up to synchronize related stakeholders’ interest in all levels. The aforementioned conditions are including simplified REDD+ regulations so that REDD+ can be adopted, existance of regional REDD+ institutions to bridge communication between central and provincial government, clear domestic funding and incentive mechanism to deal with uncertainty global agreement, as well as increasing outreach of REDD+ strategies and policies in sub-national and site levels.